1940-1948, les éditeurs québécois et l'effort de guerre - Michon, Jacques (Presses de l'Université Laval et Direction de la programmation culturelle de la BAnQ, 2009)
Keywords: Guerre; Édition

La guerre chez les poètes de l’Hexagone: Paul-Marie Lapointe, Fernand Ouellette et Jacques Brault - Parenteau, Olivier (Voix et Images, 2012)
Keywords: Poésie; Écrivains; Édition

From Bourassa to Bourassa: Wilderness to Restoration - MacDonald, L. Ian (McGill-Queen's University Press, 2002)
"From Bourassa to Bourassa is a narrative history of the Quebec Liberal Party during its wilderness years after the 1976 election of the Parti Quebecois and its subsequent restoration in 1985." "First published to critical acclaim in 1984, From Bourassa to Bourassa, 2nd edition, updates the story with Bourassa's landslide election victory in 1985 and his subsequent role in the Meech Lake Accord and the Canada-U.S. Free Trade Agreement, the two issues that largely defined the decade of the 1980s for Quebec and for Canada."--BOOK JACKET.
Keywords: Bourassa, Robert; Partis politiques

Histoire des Patriotes - Filteau, Gérard; Desbiens, Marie-Frédérique (Septentrion, 2003)
Keywords: Rébellions

Women at the Hustings: Gender, Citizenship, and the Montreal By-Elections of 1832 - Bradbury, Bettina (Rethinking Canada: the Promise of Women’s History, 2011)
Keywords: Femmes; Élections

Papineau: son influence sur la pensée canadienne: essai de psychologie historique - Circé-Côté, Ève (Mémoire des Amériques, 2002)
Keywords: Circé-Côté, Éva; Papineau, Louis-Joseph

Lettres d'un patriote condamné à mort - de Lorimier, François-Marie-Thomas-Chevalier; Nadeau, Jean-François; Fabre, Hector (Comeau & Nadeau, 1997)
Keywords: Lorimier, Chevalier de; Rébellions

George-Étienne Cartier, bourgeois montréalais - Young, Brian (Boréal, 2004)
Keywords: Bourgeoisie; Cartier, George-Étienne

In Weakness, Strength; the Spiritual Sources of Georges P. Vanier: 19th Governor-General of Canada - Vanier, Jean (Griffin House, 1975)
Keywords: Gouverneurs

Ma faiblesse, c'est ma force: un aperçu de la vie intérieure du général Georges P. Vanier, gouverneur général du Canada de 1960 à 1967 - Vanier, Jean (Bellarmin, 1992)
Keywords: Gouverneurs

René Lévesque and the Parti Québécois in Power - Fraser, Graham (McGill-Queens University Press, 2001)
Keywords: Lévesque, René; Partis politiques

Les Patriotes de 1837-1838 - David, Laurent-Olivier (Mémoire des Amériques, 2007)
Keywords: Rébellions

Écrits - Dessaulles, Louis-Antoine (Presses de l'Université de Montréal, 1994)

Georges-Émile Lapalme. Discours et écrits politiques, 1945-1981 - Lapalme, Georges-Émile (Del Busso, 2018)
Keywords: Lapalme, Georges-Émile

Discours - Parent, Étienne (Bibliothèque du Nouveau Monde, 2000)

Mes tablettes: journal d'un apothicaire montréalais, 1820-1850 - Trudeau, Romuald (Leméac, 2016)
Keywords: Apothicaires